2016
DOI: 10.1108/nlw-01-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Arab authors’ perceptions about the scholarly publishing and refereeing system used in Emerald’s library and information science journals

Abstract: Purpose The key purpose of this study is to gain an insight into the quality of the scholarly publishing and refereeing system used by Emerald’s Library and Information Science (LIS) journals from the perspectives of the Arab authors who are publishing in this wide-ranging database. It also tries to provide helpful guidance for authors to fit their authorship for publication. Design/methodology/approach Of the total 3,846 papers published in Emerald’s LIS journals in the past five years (the beginning of 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…The study also showed that most of the authors who published in predatory journals in 2016 are from Egypt and Saudi Arabia. The result was found to be consistent with the results found by Mansour (), who found that the most contributors on indexed publishing outlets are from the same two countries, which means that the population of the researchers who are engaging in scholarly publishing activities in the Middle East is based in the two countries.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The study also showed that most of the authors who published in predatory journals in 2016 are from Egypt and Saudi Arabia. The result was found to be consistent with the results found by Mansour (), who found that the most contributors on indexed publishing outlets are from the same two countries, which means that the population of the researchers who are engaging in scholarly publishing activities in the Middle East is based in the two countries.…”
Section: Resultssupporting
confidence: 90%
“…Hanafi () confirmed the results that suggest that the promotion system in the Middle East prioritizes local publishing, which discourages Arab scholars from publishing in indexed journals, leading them to publish in paid journals or predatory journals. A study by Mansour () showed that the promotion system in some Arab countries, such as Egypt and Saudi Arabia, does not encourage co‐authorship, which may explain the low number of papers authored by more than one researcher. The study also revealed that the number of scholarly papers published by Arab authors in the field of library and information science in an international database, such as Emerald, is very low compared to other nationalities.…”
Section: Arab Scholars Publishing In International Journalsmentioning
confidence: 99%
“…The study revealed that somewhat more than two-thirds of respondents had never been a second author, more than two-thirds had never been a third author, more than three-quarters had never been a fifth author and a significant percentage had never been more than a fifth author. These findings are consistent with previous research, such as Mansour's (2016) study, which discovered that the majority of Arab authors (80.9%) publishing in Emerald's LIS journals preferred sole authorship. Many of them were unhappy with the collaborative efforts.…”
Section: Discussion Of the Studysupporting
confidence: 93%